Turismo, produçâo e apropriaçâo do espaço e percepçâo ambiental: o caso de Canoa Quebrada, Aracati, Ceará. - Dantas, Shirley Carvalho (2003)
The theme in question fell about the attempt of evaluating the questions about the man x nature relationship seeking to comprehend the process that involve the output of the spaces in which the nature is urbanized. In this way, it constituted general objective of that work to understand the social action that occurs by means of distinct producers agents of the space, from a vision that privileges the environmental perception of those agents, worked taking as base substantiations brought from Yi Fu TUAN, on the principle that when you apprehend the form in which everyone perceives his environment, iti is possible to acknowledge the causes and consequences of all the process of apropriation and output of the space. The site to be studied was Canoa Quebrada, urban nucleus of the town of Aracati, one of the most famous tourist destination of the State, that experienced in the last 20 years deep arising from environmental, urban, and social transformations from the artificial valorization from the land created by the tourist activity, reflecting in a disorderly occupation of soil and predatory of the landscape. Through interviews and observations in field, sought to capture the inter-relations of these agents with the environment and between itself. The research permitted apprehend that the experiences, the feelings, the ideas, the objectives of each group defined to theirs interaction with Canoa Quebrada and, they generate consequences, sometimes, that is ignored completely and that affect the quality of life of several generations. It was possible to discover, then, that Canoa Quebrada is an abstract, a tourist and a fragmented space (LEFEBVRE) to some kinds of visitors, land´s holders, foreigners residents and to the State, but also is space lived and perceived, and, fundamentally, place, for majority of the natives and of non native brazilians residents having in mind to attribute to Canoa the meaning and value. To the peculiar ways of experimenting and interpreting Canoa Quebrada, therefore, in harmony with the spatial practices of each agent producer of their space.